Parallel G-quadruplex recognition by neomycin - Ranjan, Nihar; Arya, Dev P. (Frontiers in Chemistry, 2023)
G-quadruplex-forming nucleic acids have evolved to have applications in biology, drug design, sensing, and nanotechnology, to name a few. Together with the structural understanding, several attempts have been made to discover and design new classes of chemical agents that target these structures in the hope of using them as future therapeutics. Here, we report the binding of aminoglycosides, in particular neomycin, to parallel G-quadruplexes that exist as G-quadruplex monomers, dimers, or compounds that have the propensity to form dimeric G-quadruplex structures. Using a combination of calorimetric and spectroscopic studies, we show that neomycin binds to the parallel G-quadruplex with affinities in the range of Ka ∼ 105–108 M-1, which depends on the base composition, ability to form dimeric G-quadruplex structures, salt, and pH of the buffer used. At pH 7.0, the binding of neomycin was found to be electrostatically driven potentially through the formation of ion pairs formed with the quadruplex. Lowering the pH resulted in neomycin’s association constants in the range of Ka ∼ 106–107 M-1 in a salt dependent manner. Circular dichroism (CD) studies showed that neomycin’s binding does not cause a change in the parallel conformation of the G-quadruplex, yet some binding-induced changes in the intensity of the CD signals were seen. A comparative binding study of neomycin and paromomycin using d(UG4T) showed paromomycin binding to be much weaker than neomycin, highlighting the importance of ring I in the recognition process. In toto, our results expanded the binding landscape of aminoglycosides where parallel G-quadruplexes have been discovered as one of the high-affinity sites. These results may offer a new understanding of some of the undesirable functions of aminoglycosides and help in the design of aminoglycoside-based G-quadruplex binders of high affinity.